Respuesta :

Step-by-step explanation:

sum of three no =94

first no =X

second no x-8

third no =4(x-8)

X+(x-8)+4x-32=94

6x-40=94

6x=94-40

6x=54

X=54/6

X=9

Answer: The first number is 9, the second number is 17, and the third number is 68.

Step-by-step explanation:

Using the given information we will represent the first number by f , the second number by s, and the third number by t.

The first number is 8 less than the second  and we will represent that by the equation,   f= s-8

The third number is 4 times the second and it will be represented by the expression,  t= 4s  

We know the sum of the numbers has to equal  94 so we will add them.

The first number is s-8, the second is s, and the third is 4s.

(s - 8) + (s) + 4(s) = 94   Solve for s to find the second number.

6s - 8 = 94

    +8     +8

6s = 102    

s = 17  

The second number is 17 and we will input 17 in for s to solve for the first and third numbers.

f= 17 - 8

f= 9  

The first number is 11.

t= 4(17)

t = 68    

The third number is 68.

Check: Now add them to see if they equal to 94.

9+ 17 + 68 = 94

   94 = 94      

ACCESS MORE